E-Life: Web-Enabled Convergence of Commerce, Work, and Social Life 10th Workshop on E-Business, WEB 2011, Shanghai, China, December 4, 2011, Revised Selected Papers - Shaw, Michael J.; Zhang, Dongsong; Yue, Wei T.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the Workshop on E-Business (WEB 2011), held in Shanghai, China, on December 4, 2011. The 40 papers, which were selected from 88 submissions to the workshop, touch on topics that are diverse yet highly relevant to the challenges faced by today's e-business researchers and practitioners. They are organized in topical sections on social networks, business intelligence, and social computing; economics and organizational implications of electronic markets; and e-business systems and applications.
Keywords: Business; Production management; Information technology; Business -- Data processing; Application software; E-commerce.; Business and Management; IT in Business; e-Commerce/e-business.; Computer Appl. in Administrative Data Processing; Information Systems Applications (incl. Internet).; Operations Management; Electronic books